Optimalisasi Hasil Produksi pada Pabrik Manufaktur Furnitur dengan Metode Time and Motion Study (TMS) - Andi Jafar Wahyu Hidayat; Endang Pudji Purwanti; Aulia Nadia Rachmat (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Abstract - Increasing production quantity is the company's effort to increase the scope of production, to maximize the potential for greater product sales. The Make to Order (MTO) system used for largescale product orders has an impact on uncertain production forecasts so that good planning is needed to reach the targets. Furniture factories that have a target market for product exports, need a production time that is in accordance with the capacity of the factory. Determination of standard time is one way to increase production results. The time and motion study (TMS) method can determine the standard time by recording production tracks to get maximum production results. The results of this study indicate that the total standard time for the one seater margaret is 3,851.08 seconds. Production time for 500 products takes 67 production working days, 1000 products takes 134 production working days and 1500 products takes 201 production working days. Production calculation time using TMS has accelerated time by 11.03%, which is 477.92 seconds, compared to the existing production time, namely there is an increase in production with production acceleration of up to 9 days on 500 margaret one seater products